Whole-genome DNA methylation analysis of Chinese hamster ovary cells undergoing media adaptation - Roy, Suki; Sandhu, Jasrene Kaur; Huang, Lingzhi; Wong, Abraham; Wan, Guo Xuan; Lyko, Frank; Igwe, Emeka Ignatius; Böhl, Florian (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionChinese Hamster Ovary (CHO) cells are widely used for the production of recombinant therapeutics due to their ability to carry out human-like post-translational modifications. Media adaptation represents a key step in large-scale production to ensure optimal safety and cost efficiency. As DNA methylation is a central epigenetic mechanism underlying adaptive modulation of gene expression, we report here, for the first time, the use of high-coverage whole-genome bisulfite sequencing to generate single-base-resolution maps of CHO cells at different phases of growth in a fed-batch culture and undergoing media adaptation across four different media.MethodsA CHO cell line was adapted to four commercially available media, and their growth rates and productivity were compared with those obtained using the control medium in a 7-day batch culture. This approach resulted in the generation of n = 57 high-quality whole-genome DNA methylation datasets, which were subjected to differential DNA methylation and gene association analyses. In addition, we developed a novel DNA methylation array comprising more than 63,000 CpG methylation sites across the CHO genome, enabling streamlined and efficient DNA methylation profiling of CHO cells.ResultsAnalysis of n = 57 high-quality DNA methylation datasets revealed altered DNA methylation patterns across different phases of growth in a fed-batch culture and in response to distinct media adaptations. Specifically, adaptation to four different media resulted in highly specific methylation changes that were associated with distinct functional outcomes, including protein productivity. Finally, the customized DNA methylation microarray platform was used to validate all media adaptation-dependent epigenetic changes identified by whole-genome bisulfite sequencing (WGBS).ConclusionThese findings identify and characterize dynamic DNA methylation changes occurring during media adaptation and support their potential use as predictive indicators of CHO cell phenotypic changes in response to a dynamic culture environment. Furthermore, this work represents a valuable resource for the development of DNA methylation-based biomarkers for the optimization of CHO cell culture.